An update on the use of Raman spectroscopy in molecular cancer diagnostics: current challenges and further prospects. (4th March 2018) - Upchurch, Emma; Isabelle, Martin; Lloyd, Gavin Rhys; Kendall, Catherine; Barr, Hugh
ABSTRACT: Introduction : Cancer is responsible for an extraordinary burden of disease, affecting 90.5 million people worldwide in 2015. Outcomes for these patients are improved when the disease is diagnosed at an early, or even precancerous, stage. Raman spectroscopy is demonstrating results that show its ability to detect the molecular changes that are diagnostic of precancerous and cancerous tissue. This review highlights the new advances occurring in this domain. Areas covered : PubMed searches were undertaken to identify new research in the utilisation of Raman spectroscopy in cancer diagnostics. The areas in which Raman spectroscopy is showing promise are covered, including improving the accuracy of identifying precancerous changes, using the technology in real time, in vivo modalities, the search for a biomarker to aid potential screening and predicting the response of the cancer to the treatment regimen. Expert commentary : Many of the examples in this review are focused on Barrett's oesophagus and oesophageal adenocarcinoma as this is my area of expertise and perfectly exemplifies where Raman spectroscopy could be utilised in clinical practise. The authors discuss the areas where they believe current knowledge is lacking and how Raman spectroscopy could answer the dilemmas that are still faced in the management of cancer.